Microenvironment Elements Involved in the Development of Pancreatic Cancer Tumor - Katarzyna Gardian; Sława Janczewska; Marek Durlik (Gastroenterology Research and Practice)
Introduction. In spite of intensive research during many years, pancreatic adenocarcinoma remains one of the deadliest cancers. The surgical intervention remains main possibility of treatment because chemotherapy and radiotherapy has a minimal impact on long-term survival. We are still looking for the weak points of this devastating disease. Materials and Methods. Pancreatic tumor tissue samples were collected from 36 patients. Immunohistochemistry staining was used to evaluate expression of growth factors and immune infiltrates. Activity of MMP2 and MMP9 was assessed by gelatin zymography on 7.5% SDS-PAGE gel with 0.1% gelatin. Results. All growth factors were strongly expressed in pancreatic tumor tissue. We found that level of expression of c-Met receptor was higher for G3 tumors than for G2 tumors. Also we found that active MMP2 was present at all stages of tumor while active MMP9 just at more advanced tumors. Abundant immune cells infiltration was distinctive for tumor tissue, especially macrophages were infiltrating tumor tissue. We found that amount of macrophages was associated with lymph nodes metastases. Conclusion. In our research we demonstrated that among many factors influencing tumor microenvironment c-Met receptor, infiltrating macrophages and MMP2 have significant influence on development and invasion of pancreatic cancer.